4CPS-235 A mobile team of clinical pharmacists in digestive and urological surgery units: results and satisfaction after 9 months. (2nd March 2018) - Bernard, A; Allaire, N; Mocquard, J; Serandour, N; Corbineau, E
Abstract : Background: Medication errors frequently occur in surgical units, partly due to the large number of prescribers (surgeons, anaesthetists, dieticians) and to potential interactions between anaesthesia and medications taken by the patient. In order to reduce these errors in digestive and urological surgery, a mobile team of clinical pharmacists has been deployed. The activities (medication reconciliation (MR), pharmaceutical analysis and optimisation at the patient's bedside) are led by a pharmacist, a pharmacy resident and two students. Purpose: The objective of our study was to evaluate the impact of a clinical pharmacy organisation on patient care safety and the satisfaction of physicians and nurses in digestive and urological surgical units (84 beds). Material and methods: Over 9 months, all pharmaceutical interventions (PI) were registered and categorised according to the French Society of Clinical Pharmacy (SFPC). The number of PIs leading to a prescription's modification was recorded. A satisfaction survey was performed 8 months after the deployment: 104 professionals (surgeons, residents, anaesthesiologists, nurses) were interviewed to evaluate their satisfaction. The survey included questions regarding the quality of information provided by the pharmaceutical team and the impact on patient safety. Results: Since November 2016, 2808 patients benefited from the pharmaceutical team, and 1, 334 PIs have been performed. Those PIs concerned 23.5% of the patients: most of them were related to inadvertently omitted medications (38%) or incorrect posology (32%). 1159 (87%) PIs were accepted by the prescriber and led to a prescription modification. Regarding the satisfaction survey, we collected 58 answers: 96% of the respondents were satisfied by the actions of the team and 98% agreed that those activities increased patient care safety. Furthermore, 94% thought that other surgery units should benefit from the same activities. Conclusion: The high acceptance rate of PIs demonstrates the importance of the pharmaceutical team in improving healthcare safety regarding medications. The satisfaction survey confirms that the pharmaceutical offer is well accepted and useful to healthcare professionals. Finally, since the deployment of the team, we observed a simultaneous decrease in medications expenses in the units (−17%), allowing continuity of the actions taken and extension of the team in other surgical units. No conflict of interest